Pengembangan Lembar Kerja Peserta Didik Berbasis Problem Based Learning Terintegrasi Etnosains Untuk Melatih Literasi Sains dan Berpikir Kreatif - Nurul Hidayah; Agil Al Idrus; Agus Abhi Purwoko (Jurnal Penelitian Pendidikan IPA, 2025)
This research aims to develop appropriate student worksheet to train science literacy and creative thinking. This student worksheet was developed based on Problem Based Learning integrated with ethnoscience in elemental, compound, and mixed materials. This research focuses on the validation of student worksheet that has been developed to ensure its quality and feasibility as a teaching material. This type of research is Research and Development (R&D) and uses the ADDIE (analysis, design, development, implementation, and evaluation) model. The subject of the study is Grade VII junior high school. The validation results in the aspect of content feasibility with Aiken V index obtained score of 0.93 with a very valid category, a language feasibility aspect of 0.90 with a very valid category, a presentation feasibility of 0.86 with a very valid category, a display feasibility of 0.93 with a very valid category, and an ethnoscience orientation aspect of 0.92 with a very valid category. The average overall validation score is 0.91 with a very valid category. The reliability results in the aspects of content feasibility, language feasibility, presentation feasibility, display feasibility, and ethnoscience orientation are reliable with an average score of 93%. Based on these results, the student worksheet based on ethnoscience-integrated Problem Based Learning is very feasible (valid and reliable) to be used in learning activities to train science literacy and creative thinking. This study contributes to the practice of contextual science education in secondary schools by providing a validated and culturally relevant learning resource that enhances both literacy and creativity in science learning.